2021
DOI: 10.3389/fpubh.2021.643807
|View full text |Cite
|
Sign up to set email alerts
|

Coping During the COVID-19 Pandemic: A Qualitative Study of Older Adults Across the United States

Abstract: Objective: Older adults may struggle with stresses and daily life challenges associated with the Coronavirus Disease 2019 (COVID-19) pandemic. Yet they may also utilize emotional and behavioral coping strategies. This qualitative paper aims to identify ways of coping with worries and stress during the pandemic from the perspectives of older adults in the United States.Methods: The COVID-19 Coping Study recruited 6,938 adults aged ≥55 through online multi-frame sampling from April 2-May 31, 2020 across all 50 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
100
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 37 publications
18
100
1
3
Order By: Relevance
“…As expressed by the participants, such practices helped them manage stress, limit their fears of infection, and keep busy during the pandemic, allowing them to adapt and live normally throughout the crisis. This finding is consistent with that reported by Finlay et al 15 ) who found that older adults often used and identified coping strategies to be resilient amidst the COVID-19 crisis, including changing habits, following public health recommendations, and avoiding health-restricting behaviors (e.g., overeating), all of which encouraged them to have positive adjustments as individuals. Furthermore, Igarashi et al 34 ) reported increased self-awareness as a coping mechanism that was unique to older adults.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expressed by the participants, such practices helped them manage stress, limit their fears of infection, and keep busy during the pandemic, allowing them to adapt and live normally throughout the crisis. This finding is consistent with that reported by Finlay et al 15 ) who found that older adults often used and identified coping strategies to be resilient amidst the COVID-19 crisis, including changing habits, following public health recommendations, and avoiding health-restricting behaviors (e.g., overeating), all of which encouraged them to have positive adjustments as individuals. Furthermore, Igarashi et al 34 ) reported increased self-awareness as a coping mechanism that was unique to older adults.…”
Section: Discussionsupporting
confidence: 91%
“…To produce novel insights and a more detailed understanding of complex realities, diverse lived experiences, and how older people are making sense of and coping with what is happening around them during this crisis, qualitative insights are needed, influencing their resiliency and adaptation to such difficult situations as the COVID-19 pandemic. 15 ) Moreover, understanding these factors and mechanism that drives older adult’s internal resilience during such situations could guide healthcare practitioners including nurses in providing an effective and efficient intervention approaches to such special population who have been greatly affected by this pandemic illness. 6 , 16 )…”
Section: Introductionmentioning
confidence: 99%
“…4 ; Mann–Whitney U test: n = 4728; U = 0.58; p < 1e−21). Using positive coping strategies, such as exercise, was also reported for the elderly US population [ 24 ]. Intriguingly, in contrast with all other types of concern and distress, older respondents scored higher on the national-global concern scale (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the protective measures were designed to protect older persons from falling ill, being confined to one’s home may pose a threat to wellbeing [ 3 ]. Some older adults adapted to sheltering at home [ 25 ], while others found ways to replace blocked out-of-home activities with alternative activities, such as physical exercise outdoors [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%